EFFECT OF PURWOCENG EXTRACT ON THE EXPRESSION OF NITRIC OXIDE NEURONAL SYNTHASE IN PENILE TISSUE OF WHITE MALE RATTUS NOVERGICUS - Pratama, I Gede Andre Arda; Danarto, H R (Indonesian Journal of Urology, 2018)
Objective: To know the effect of purwoceng extract (Pimpinella alpine) on the expression of neuronal nitric oxide synthase (nNOS) in the penile tissue of white male rats (Rattus novergicus) through immunohistochemical examination. Material & Methods: Animal experiments consisted of 27 male rats, three months of age with a mean body weight of approximately 200 grams were divided into three groups randomly, one group consisted of 10 rats. Treatment 1 rats receive Pimpinella alpina extract with 50 mg/ml, Treatment 2 rats receive Pimpinella alpina extract with 100 mg/ml. In the control group rats receive aquadest as much as 1 ml. Results: In the control group the average is 75.67, in the treatment group 1 is 113, and in group 2 is 181.44. The difference in treatment between groups was performed using one-way ANOVA test. Between control and treatment groups 1 the different is significant with p value of 0.013 (p<0.05). The mean expression of nNOS between treatment groups 1 and 2 differ significantly with p=0.00 (p<0.05). Conclusion: Purwoceng extract (Pimpinella alpine) can increase the expression of nNOS on NANC nerve fibers (nonadrenergic noncholinergic) in the corpora cavernosa of the penis that causes smooth muscle relaxation in penile erection.